2009
DOI: 10.1007/s12594-009-0075-z
|View full text |Cite
|
Sign up to set email alerts
|

Mapping groundwater vulnerable zones using modified DRASTIC approach of an alluvial aquifer in parts of central Ganga plain, Western Uttar Pradesh

Abstract: A detailed hydrogeological and hydrochemical study was carried out in Yamuna-Krishni sub-basin which is a part of the vast central Ganga plain. Groundwater is the major source of water supply for agricultural, domestic and industrial uses. The excess use of groundwater has resulted in depletion of water levels. The groundwater quality, too, has deteriorated in areas dominated by industrial activity. This has led to the preparation of a groundwater vulnerability map in relation to contamination. Groundwater vul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(24 citation statements)
references
References 6 publications
0
24
0
Order By: Relevance
“…Khan et al (2010) assessed the groundwater vulnerability in parts of Indo-Gangetic Plains and observed that quality and quantity of shallow aquifers to a large extent were governed by land use patterns. Umar et al (2009) generated aquifer vulnerability potential map of an alluvial aquifer in parts of Central Ganga Plain, Western Uttar Pradesh using DRASTIC approach which showed that 7, 40 and 53 % of the study area falls in low, medium and high to very high vulnerable zones, respectively. Rahman (2008) delineated groundwater vulnerable zones in shallow aquifers in Aligarh and surrounding areas.…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al (2010) assessed the groundwater vulnerability in parts of Indo-Gangetic Plains and observed that quality and quantity of shallow aquifers to a large extent were governed by land use patterns. Umar et al (2009) generated aquifer vulnerability potential map of an alluvial aquifer in parts of Central Ganga Plain, Western Uttar Pradesh using DRASTIC approach which showed that 7, 40 and 53 % of the study area falls in low, medium and high to very high vulnerable zones, respectively. Rahman (2008) delineated groundwater vulnerable zones in shallow aquifers in Aligarh and surrounding areas.…”
Section: Introductionmentioning
confidence: 99%
“…Identification of highly susceptible areas is a first and necessary step toward preventing groundwater pollution. This will allow a given region to be classified into sub-regions in terms of their vulnerability intensity and relevant measures to be designed that will prevent pollution from reaching vulnerable areas (Mohammadi et al 2009;Umar et al 2009;Rezaei et al 2013). In this context, the inclusion of vulnerability maps in groundwater quality protection plans would be beneficial, along with the discussion of groundwater contamination risk with stakeholders that include politicians, entrepreneurs, opinion makers, general public (Valle Junior et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It has a significant impact on the amount of recharge water which can infiltrate into the ground and hence, influence the ability of a contaminant to move vertically into the vadose zone (Umar et al 2009). There are six types of soil present in the study area such as genteelly loamy, coarse loamy, very genteelly slopping loamy, fine loamy, fine soil with loamy surface texture and moderate erosion, fine loamy soil on very genteelly slopping land with loamy surface texture.…”
Section: Soil Mediamentioning
confidence: 99%
“…GIS can be useful for taking quick decisions as graphical representation would be easy to take a policy decision by the makers (Singh et al 2013b). GIS techniques have been becoming the most commonly used platform for assessment of groundwater vulnerability (Al-Adamat et al 2003;Becker 2006;Almasri 2008;Rahman 2008;Umar et al 2009;Saha and Alam 2014;Nasri et al 2015) along with the use of remote sensing techniques (Yeh et al 2006), statistical method (Burkart et al 1999;Fred et al 2002), environmental isotope and water chemistry method (Sadek and El-Samie 2001), and fuzzy mathematical method (Zhou et al 2010). The aim of the study is proper understanding of the aquifer system and hydro-geological setting of the area for development and safe exploitation of groundwater.…”
Section: Introductionmentioning
confidence: 99%